THE INFLUENCE OF CUSTOMER EXPERIENCE IN MOBILE CART SERVICES AND MOBILE APPLICATION INTEGRATION ON CUSTOMER LOYALTY AT KOPI JAGO - Fabio Ar’riva Rachman; Kevin Arliantoro; Yehezkiel Bryan Pratama Firdiyanto (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of customer experience on mobile cart services and application integration on customer loyalty of Kopi Jago in Jakarta. Using a quantitative causal approach, data were gathered via digital questionnaires distributed to consumers. Out of 120 respondents collected, a purposive screening identified 53 clean respondents who actively use both the mobile cart and the application. Data analysis was conducted using Variance-Based Structural Equation Modeling (PLS-SEM) via SmartPLS. The descriptive results show high satisfaction for the physical mobile cart experience, while application utilization is highly rated but faces an adoption gap among manual buyers. Furthermore, price sensitivity remains a critical constraint on long-term loyalty, as scores drastically dropped regarding potential price increases. This study provides managerially critical insights into balancing physical retail mobility with digital application ecosystem optimization within an omnichannel strategy in the modern coffee cart industry.